Application and synthesis of thiazole ring in clinically approved drugs - Niu, Zhen-Xi; Wang, Ya-Tao; Zhang, Sheng-Nan; Li, Yan; Chen, Xiao-Bing; Wang, Sai-Qi; Liu, Hong-Min (European journal of medicinal chemistry, 2023)
The development of heterocyclic derivatives has progressed considerably over the past few decades, and many new agents of synthetic and natural origin have been produced. Among heterocyclic compounds, thiazole is a unique five-membered heterocyclic motif characterized by nitrogen and sulfur atoms, which is widely used as an important core skeleton in a variety of pharmaceutically important compounds due to their diverse biological activities, such as antibacterial, antivirus, and antifungal. To the best of our knowledge, more than 90 thiazole-containing derivatives have been currently under clinical investigation, and some thiazole analogs have been approved to treat various diseases. As the potentially privileged scaffolds, thiazole derivatives can be further extensively explored to search for new drugs characterized by improved therapeutic efficacy and similar biological targets. This review aims to outline the applications and synthetic routes of some representative thiazole-containing drugs approved in the clinic, which may guide medicinal researchers to rationally design more effective thiazole-containing drug candidates. [Display omitted] •Thiazole ring is widely used in many drugs to treat various diseases.•Recent advances in thiazole-containing drugs have been summarized.•The clinical applications and synthetic routes of 33 thiazole-containing drugs are highlighted.•Summary and prospect are briefly discussed to guide future design of thiazole-containing drugs.